2018
DOI: 10.1038/s41598-018-19308-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinome and phosphoproteome of high-grade meningiomas reveal AKAP12 as a central regulator of aggressiveness and its possible role in progression

Abstract: There is a need to better understand meningioma oncogenesis for biomarker discovery and development of targeted therapies. Histological or genetic criteria do not accurately predict aggressiveness. Post-translational studies in meningioma progression are lacking. In the present work, we introduce a combination of mass spectrometry-based phosphoproteomics and peptide array kinomics to profile atypical and anaplastic (high-grade) meningiomas. In the discovery set of fresh-frozen tissue specimens (14), the A-kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 63 publications
0
27
0
3
Order By: Relevance
“…Also, we validated targets like AHNAK, tumor-specific proteins like TPD52L2, TS101. Peptides corresponding to NEK9, SELENBP1 which were previously reported as a marker for aggressivity via two independent proteomics study were also optimized and monitored across the meningioma patient cohort ( 5 , 7 ). We further monitored the levels of PI3K-Akt and Integrin family members like EIF4G1 and CKAP4 ( Figure 6 , Supplementary Data 7 , 9 , and Supplementary Figures 5 , 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we validated targets like AHNAK, tumor-specific proteins like TPD52L2, TS101. Peptides corresponding to NEK9, SELENBP1 which were previously reported as a marker for aggressivity via two independent proteomics study were also optimized and monitored across the meningioma patient cohort ( 5 , 7 ). We further monitored the levels of PI3K-Akt and Integrin family members like EIF4G1 and CKAP4 ( Figure 6 , Supplementary Data 7 , 9 , and Supplementary Figures 5 , 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Though limited in number, there have been recent studies that have uncovered newer insights into the way the tumors behave using several proteomics approaches ( 5 8 ). We earlier reported an elevation in the levels of AHNAK, Gelsolin, S100 family of proteins, and several other proteins like CKAP4 that were specific to particular grades of meningiomas ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have shown that Gravin loss is linked to defective mitoses in a variety of cancer cell lines (35,36). Recent phosphoproteomics studies further implicate this anchoring protein as a potential prognostic biomarker for high-grade meningiomas (35,36). Our discovery that Gravin-ablated cells display an enhanced pole-to-pole asymmetry of γ-tubulin provides additional clues into how protein scaffolds safeguard cell division events ( Figure 3F-K).…”
Section: Discussionmentioning
confidence: 55%
“…Our findings argue that Gravin-mediated signaling further contributes to this process. Other investigators have shown that Gravin loss is linked to defective mitoses in a variety of cancer cell lines (35,36). Recent phosphoproteomics studies further implicate this anchoring protein as a potential prognostic biomarker for high-grade meningiomas (35,36).…”
Section: Discussionmentioning
confidence: 94%
“…Proteomics can detect the differential expression of proteins in different grades or types of meningiomas ( Supplementary Table 3 ) ( 56 58 ). As early as 2006, the pure meningioma cell population was sequenced to indicate the differentially expressed proteins of each WHO grade meningioma.…”
Section: Proteomicsmentioning
confidence: 99%